Work function engineering of electrodes via electropolymerization of ethylenedioxythiophenes and its derivatives - Shi, Yumeng (2012)
The work functions of two commonly used electrodes, Au and indium-tin-oxide (ITO), can be modified by surface-electropolymerization of ethylenedioxythiophenes (EDOT) or its derivatives. The resulting work function is tunable continually by varying the electropolymerization condition. The value of work function of ITO (or Au) electrodes can be adjusted to decrease by 0.6 eV (or increase by 0.4 eV) when the deposited EDOT film is thin (<40 nm). By contrast, when the EDOT film deposited with thickness greater than 40 nm, the work function is controlled by the intrinsic property of the polymers regardless of the electrode materials. A diode devices with EDOT–COOH modified on ITO surface demonstrates the possibility of improving contact property in organic electronics using the proposed method.